Some Extensions of Fixed Point Results over Quasi-JS-Spaces - Maha Noorwali; Hamed H. Alsulami; Erdal Karapınar (Journal of Function Spaces)
We introduce the notion of quasi-JS-metric space. After defining the basic topological properties of quasi-JS-metric space, we investigate fixed point of certain mapping in the frame of complete quasi-JS-metric space. Our results unify and cover several existing fixed point theorems in distinct structures (such as standard quasi-metric spaces, quasi-b-metric spaces, dislocated quasi-metric spaces, and quasi-modular spaces) in the literature.